The Birth of an Ultraluminous X-Ray Source in M83 - Soria, Roberto; Kuntz, K.; Winkler, P.; Blair, W.; Long, K.; Plucinsky, P.; Whitmore, B. (Institute of Physics Publishing, Inc., 2012)
A previously undetected (LX < 1036 erg s–1) source in the strongly star-forming galaxy M83 entered an ultraluminous state between 2009 August and 2010 December. It was first seen with Chandra on 2010 December 23 at LX ≈ 4 × 1039 erg s–1 and has remained ultraluminous through our most recent observations in 2011 December, with typical flux variation of a factor of two. The spectrum is well fitted by a combination of absorbed power-law and disk blackbody models. While the relative contributions of the models vary with time, we have seen no evidence for a canonical state transition. The luminosity and spectral properties are consistent with accretion powered by a black hole with M BH ≈ 40-100 M ☉. In 2011 July we found a luminous, blue optical counterpart that had not been seen in deep Hubble Space Telescope observations obtained in 2009 August. These optical observations suggest that the donor star is a low-mass star undergoing Roche lobe overflow, and that the blue optical emission seen during the outburst is coming from an irradiated accretion disk. This source shows that ultraluminous X-ray sources (ULXs) with low-mass companions are an important component of the ULX population in star-forming galaxies and provides further evidence that the blue optical counterparts of some ULXs need not indicate a young, high-mass companion, but rather that they may indicate X-ray reprocessing.